Dynamic succession of the quantity and composition of epiphytic microorganisms at different growth stages on rice surface - Huang, Lijuan; Zhang, Zhifei; Mu, Lin; Liu, Xiong; Sun, Rongji; Gao, Wenjing; Chen, Guihua (Frontiers in Microbiology, 2024)
The quality of silage is uneven, which is due to the difference of epiphytic microorganisms of raw materials. To improve the quality of fermentation, the quantity and composition of epiphytic microorganisms are usually analyzed to better prepare silage. Therefore, the aim of this research was to investigate the effect of growth stage on the quantity and community diversity of rice epiphytic microorganisms. Results showed that there were significant differences in the quantity of epiphytic microorganisms at different growth stages. The LAB and aerobic bacteria were the highest at the flowering stage, the yeast was the highest at the milk ripening stage, and the mould was the highest at the full ripening stage. And the growth stage also had a great influence on the composition of epiphytic bacterial community, at the phylum level, it was mainly composed of Proteobacteria. And at the genus level, Pantoea, Acinetobacter, Pseudomonas and Chryseobacterium were dominanted at the flowering stage; Pantoea, Stenotrophomonas and Sphingobacterium were dominanted at the milk ripening stage; Acinetobacter, Pantoea, Chryseobacterium and